2018
DOI: 10.1186/s12879-018-3456-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of bone and joint tuberculosis in native and migrant population in Shanghai during 2011 to 2015

Abstract: BackgroundChina had the third highest burden of tuberculosis population in the world. Bone and joint tuberculosis was a major part and its characteristics were rarely discussed before. This study was designed to review the characteristics and management of bone and joint tuberculosis among native and migrant population in Shanghai, China during 2011–2015.MethodsA retrospective analysis of the patient clinical records on their demographic information, clinical features and treatment was conducted from three ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
16
2
Order By: Relevance
“…With the advent of anti-tuberculosis drugs, tuberculosis has gradually been effectively controlled. Bone and joint tuberculosis accounts for about 10% of extrapulmonary tuberculosis [3,12]. Spine tuberculosis, hip tuberculosis, and knee tuberculosis account for the majority of bone and joint tuberculosis, while shoulder tuberculosis is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of anti-tuberculosis drugs, tuberculosis has gradually been effectively controlled. Bone and joint tuberculosis accounts for about 10% of extrapulmonary tuberculosis [3,12]. Spine tuberculosis, hip tuberculosis, and knee tuberculosis account for the majority of bone and joint tuberculosis, while shoulder tuberculosis is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis caused by mycobacterium tuberculosis has been accompanied by the development of human civilization.With the advent of anti-tuberculosis drugs, tuberculosis has gradually been effectively controlled. Bone and joint tuberculosis accounts for about 10% of extrapulmonary tuberculosis [2,8,9] . Spine tuberculosis, hip tuberculosis and knee tuberculosis account for the majority of bone and joint tuberculosis, while shoulder tuberculosis is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Of cases with extra-pulmonary TB, 10%-25% have musculoskeletal involvement [3]. The most com monly affected site of extra-pulmonary TB infection is the spine, followed by the hip, knee, and ankle/foot [4,5]. Due to its non-speci c presentation TB of the knee is often reaches a very advanced state before a de nite diagnosis is made, which then leads to a poor prognosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…While TKA has clear bene ts as a treatment modality, there is no consensus on the appropriate treatment regimens for patients with osteoarticular tuberculosis [5]. For the timing of surgery, some authors suggested that TB should be inactive for several years prior to performing a TKA, while others proposed a much shorter interval [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation